2019
DOI: 10.1021/acs.jnatprod.9b00176
|View full text |Cite
|
Sign up to set email alerts
|

Opportunities and Limitations for Untargeted Mass Spectrometry Metabolomics to Identify Biologically Active Constituents in Complex Natural Product Mixtures

Abstract: Compounds derived from natural sources represent the majority of small-molecule drugs utilized today. Plants, owing to their complex biosynthetic pathways, are poised to synthesize diverse secondary metabolites that selectively target biological macromolecules. Despite the vast chemical landscape of botanicals, drug discovery programs from these sources have diminished due to the costly and time-consuming nature of standard practices and high rates of compound rediscovery. Untargeted metabolomics approaches th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
64
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 67 publications
(66 citation statements)
references
References 84 publications
1
64
0
1
Order By: Relevance
“…For pipelines integrating complex multilayer information, the use of validated bioactive reference standards spiked in extracts is highly recommended to evaluate the efficiency of the prioritisation strategy envisioned. 6 When prioritisation is not directly connected to given bioactivity results but aims at nding novel chemodiverse NPs, the virtual screening of scaffolds (docking, modelling chemical space, etc.) obtained may represent an alternative means to valorise the new chemical entities discovered.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…For pipelines integrating complex multilayer information, the use of validated bioactive reference standards spiked in extracts is highly recommended to evaluate the efficiency of the prioritisation strategy envisioned. 6 When prioritisation is not directly connected to given bioactivity results but aims at nding novel chemodiverse NPs, the virtual screening of scaffolds (docking, modelling chemical space, etc.) obtained may represent an alternative means to valorise the new chemical entities discovered.…”
Section: Resultsmentioning
confidence: 99%
“…This shows that data-processing approaches (data transformation and model simplication tools using a variance cut-off) have signicant impacts on model capacities to detect active constituents in CNEs. 6 Applications of such methods reveal their interesting potential as well as their current limitations. This also highlights the fact that they must be validated prior to implementation in prioritisation workows to assess complex botanical mixtures.…”
Section: Hsqc Nmr Metabolite Proling Of 39 Extracts Frommentioning
confidence: 99%
See 1 more Smart Citation
“…For example, approximately~6500 individual compounds, 55-57% of the total compounds detected by a UPLC-TOF-MS metabolomics study [90], have been reported to be similar across multiple cranberry cultivars. These values are likely to be underestimates, however, as this study was limited by the inherent limitations of all metabolomics methods [91] and therefore focused on a relatively small subset of all possible phytoconstituents. Comparisons of chemical complexity in relation to bioactivity are further influenced by the disregard typically given to primary metabolites and compounds of relatively high MW (>1000 Da), and by the relative inability of any one detection or analysis method to identify or characterize all chemical components present [92].…”
Section: Common Chemical Components Of Cranberry and Related Speciesmentioning
confidence: 99%
“…The detection of soluble oligosaccharides in urine is further complicated by structural features and solution behaviors that require the application of specialized detection techniques such as those used previously for this chemical class [158,172,176,180,184]. Many modern, standard, high-throughput metabolomics techniques are currently unable to detect soluble neutral oligosaccharides (DP 3-10) in biofluids such as urine or plasma due to methodological and parameter limitations [91,92,172,185,186]. Such platforms are typically focused on small molecule (<1000 Da) isolation, and underivatized neutral oligosaccharides are invisible to detection methods such as UV and are poorly ionized in GC-MS or LC-ESI-MS [28,172].…”
Section: Detection and Analysis Of Soluble Oligosaccharide Componentsmentioning
confidence: 99%